The Relationship Between Ammonia Levels and the Abundance of Phytoplankton in the morning and evening in Ujung Piring Bangkalan Estuary - Syarifah, Wasiqatus; Zainuri, Muhammad; Indriyawati, Novi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
The density of community activities around the Ujing Piring Bangkalan estuary has the potential to produce waste containing ammonia which is very dangerous for the environment and causes a decrease in water quality and threatens the existence of aquatic organisms including phytoplankton. The purpose of this study was to determine the relationship between ammonia levels and the abundance of phytoplankton in the morning and evening in the Ujung Piring Bangkalan estuary. The sampling time was carried out in the morning (08.00-09.30 WIB) and afternoon (15.00-16.30 WIB) three times in three weeks using 10 micron plankton nets in the Ujung Piring Bangkalan estuary waters. The sampling method used a purposive sampling method with phytoplankton analysis using the census method and continued with statistical tests using the linear regression method. The relationship between ammonia levels and phytoplankton abundance in the morning and evening were 0.1537 with a percentage of 15% and 0.0593 with a percentage of 0.05%, respectively. This value states that ammonia levels have a negative correlation with the abundance of phytoplankton in the morning and evening in the Ujung Piring Bangkalan estuary